Efektivitas Penggunaan Media Jeopardy Game dalam Evaluasi Maharah Qira’ah - Satyaningrum, Retnowati; Ihsan, Muhammad; Daroini, Slamet (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2024)
This research is based on the finding that the use of media at MTs Ar-Rosydiyyah Mambaul Ulum Sampang is still classified as less interesting in Arabic language learning. Therefore, this study was conducted to test the effectiveness of the use of Jeopardy Game media on student learning evaluation to improve Maharah Qiroah in Arabic language learning. This research method is quantitative research with the type of quasi-experimental research. The research design used was one group pretest-posttest design. The data collection techniques used were interviews and tests. Data analysis used the mean test, Paired Sample T Test, and N Gain Score test. Based on the data obtained and calculated, the Sig value is known. 0.001 < 0.05, which means that there is a difference in the average results of students' reading abilities. The N-Gain Score test was carried out to test the effectiveness of the Jeoprady Game in evaluating learning and obtained a percentage of 80.9970 which was in the interval > 76 so it was in the